2005
DOI: 10.1021/ma0485989
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of Shear-Induced Crystal Nucleation Precursors

Abstract: The relaxation process of shear-induced crystal nucleation precursors has been investigated in a temperature range slightly above the melting point using a series of commercial grade isotactic poly(1-butene)s with different molecular weights. Development of transcrystalline morphology from the surface of a fiber pulled through the molten polymer is ascribed to high concentration of ordered clusters promoted by the alignment of chain segments under the high-intensity shear flow at the fiber−melt interface. Shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
183
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(204 citation statements)
references
References 49 publications
(131 reference statements)
13
183
2
Order By: Relevance
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
See 1 more Smart Citation
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
“…In this regard, the studies of Azzurri and Alfonso. 90 and Zuo et al 92 deserve a special mention; in a series of well-designed experiments, they systematically investigated the relaxation behavior of shear-induced precursors in iPB melts of different molecular weight and in bimodal PE blends containing a high molecular weight species of narrow molecular weight distribution, respectively. Both studies showed that the long chains are primarily responsible for the memory of ordered structures.…”
mentioning
confidence: 99%
“…[49][50][51] By performing fiber-pulling experiments, and using the cylindritic morphology as a marker for the presence of high linear nucleation density, it was possible to determine the lifetime of shear-induced nucleation precursors in various semicrystalline polymers at several temperatures. 49,50 The results were in good agreement with those previously reported by Janeschitz-Kriegl et al [40][41][42] Further experiments, performed on i-PBu-1 and i-PS, have shown that the characteristic relaxation time is strongly dependent on the weight-average molar mass of the polymer, both for polydispersed grades and narrow fractions. 50,52 A mechanism for precursor's dissolution, based on the detachment of chain stems from the lateral surface of cylindrical clusters, was proposed to explain the gathered experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“…A good level of knowledge has been reached and it is well established that application of flow fields before and/or during polymer solidification results in a large increase of nucleation density and, as a consequence, of the overall crystallization rate [1][2][3]7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The application of flow promotes alignment of macromolecular chains along the flow direction, generating oriented nano-ordered aggregates which act as nuclei at the crystallization temperature [4][5][6][12][13][14][15][16][17][18][19][20]. FIC studies have been addressed to investigate the role of molecular parameters (composition [21][22][23], molar mass [24][25][26][27][28][29][30][31], etc) and flow conditions [11][12][32][33][34] on the crystallization kinetics of polymers, mainly of polyolefins.…”
Section: Introductionmentioning
confidence: 99%